Method for measuring scratch-induced metal surface plastic rheological mode based on DIC
Through DIC-based measurement methods, the scratch-induced plastic rheology mode of titanium alloy under different loads was studied, which solved the error problem in the research on the deformation behavior of titanium alloy and improved its wear resistance.
Patent Information
- Application Number
- CN202411818133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-11
AI Technical Summary
There are errors in the research on the surface deformation behavior of existing titanium alloys under high loads, and their wear resistance is poor, which limits its application range.
The plastic rheology mode measurement method based on DIC is used to measure the plastic rheology mode of the metal surface layer. The high-speed camera is used to capture the scratching process and use DIC technology to perform strain analysis. Combined with the abrasive mark morphology analysis, the plastic rheology mode under different loads is studied.
Real-time observation of the surface strain changes of titanium alloy is achieved, and the plastic rheology mode under different loads is accurately analyzed, which helps to reveal the friction and wear mechanism and improve the wear resistance of titanium alloy.
Smart Images

Figure CN119715216A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tribological performance testing methods for metal materials, and in particular relates to a method for measuring a scratch-induced plastic rheological mode of a metal surface layer based on DIC. Background Art
[0002] Titanium and titanium alloys, as one of the lightweight structural materials, have excellent properties such as high toughness, low electrical conductivity, high specific strength, good corrosion resistance and biocompatibility. They have become indispensable and important materials in the fields of aerospace, automotive energy, biomedicine and chemical industry. However, titanium alloys have low strength and poor wear resistance, which limits their application scope to a certain extent. At present, the scratch test is one of the most effective methods to study the surface deformation behavior of metal structural materials under high loads. Studies have pointed out that as the scratch-induced surface plastic rheological mode changes from uniform laminar flow to chaotic eddy flow, obvious material accumulation appears at the front end of the wear mark, the wear mark surface is relatively rough, and there are a lot of delamination and microcrack damage. It can be seen that clarifying the scratch-induced metal surface strain field distribution and plastic rheological mode is of great significance for revealing the friction and wear mechanism of the alloy.
[0003] Imaging technology that uses imaging equipment to capture information intuitively for analysis with appropriate exposure time and frame rate is an effective method to study the strain distribution in the plastic deformation zone. Among them, particle image velocimetry (PIV) is an effective technology for measuring strain fields. PIV is a transient, multi-point, non-contact fluid mechanics velocimetry method that indirectly measures the transient velocity distribution of the flow field by measuring the displacement of tracer particles in a known extremely short time interval. PIV technology is often used to study the elastic-plastic deformation behavior and chip formation mechanism of materials during cutting. However, PIV technology requires the use of laser to irradiate the measured flow field area, which has high requirements for laser energy. Too low laser pulse energy will lead to insufficient exposure of the high-speed camera, making it impossible to clearly image the tracer particles. Too high laser energy will produce strong laser reflection, which will also affect the measurement accuracy. For scratch strain analysis, in addition to the error caused by laser energy, the depth of surface scratch-induced strain is relatively small, and the displacement of tracer particles is not obvious, resulting in relatively insufficient accuracy of PIV technology, which leads to large errors in friction strain measurement results. Summary of the invention
[0004] The purpose of the present invention is to provide a DIC-based method for measuring the plastic rheological mode of metal scratching, including using a high-speed camera to shoot the scratching process and using DIC technology to perform strain analysis. Combined with the analysis of the wear scar morphology of the pure titanium surface, the friction and wear mechanism can be studied more deeply.
[0005] The technical solution to achieve the purpose of the present invention is: a method for measuring the scratch-induced plastic rheological mode of a metal surface based on DIC, comprising the following steps:
[0006] Step (1): preparing a rectangular TA1 commercially pure titanium sample;
[0007] Step (2): spraying a spot on the sample observation surface;
[0008] Step (3) using the surface adjacent to the observation surface as the scratching surface;
[0009] Step (4): applying scratches to the scratched surface by a friction tester, and recording the scratches with a high-speed camera to obtain a scratching video;
[0010] Step (5): Calculate the strain magnitude in the deformation area based on the scratching video;
[0011] Step (6): draw a strain distribution curve of the surface layer of TA1 along the scratching direction;
[0012] Step (7): observing the morphology of the wear scar on the TA1 surface scratched under different loads by scanning electron microscopy;
[0013] Step (8): Determine the type of plastic rheology.
[0014] Furthermore, in step (1), the sample size is 5±0.5 mm×5±0.5 mm×2±0.2 mm.
[0015] Furthermore, step (2) is specifically as follows: use a 0.5 mm caliber spray gun to spray a layer of white paint on the surface so that the metallic luster of the sample is completely covered; then use a 0.18 mm caliber spray gun to spray black paint spots on the surface, the spots are randomly distributed, the average diameter is controlled below 20 μm, and the spot distribution accounts for 80±5% of the white paint area.
[0016] Furthermore, the high-speed camera in step (4) selects a five-fold lens as a magnifying lens and a 100W LED light source as an illumination light source.
[0017] Furthermore, the scratching in step (4) is specifically performed by using a conical diamond scratching head with a tip cone angle of 120° and a diameter of 0.2 mm, setting the scratching speed to 0.1 mm / s, the scratching distance to 1 mm, setting the loading time to 10 s, the holding time to 5 s, and the scratching time to 10 s.
[0018] Furthermore, in step (4), a high-speed camera is used to record the scratching video as follows: loads of 2N, 10N, and 50N are selected, the image resolution is set to 2560×1920, the frame rate is set to 200fps, and the video is saved for 15s; the friction machine is started, and the scratching head is pressed into the sample surface and 1s before it starts to slide is used as the shooting starting point, and the video is saved after the 15s shooting time is over.
[0019] Furthermore, step (5) is specifically as follows: sorting and arranging the scratching videos and importing them into the DIC analysis program, selecting the strain change region within 100 μm thickness from the scratched surface, defining the starting point, and calculating the strain magnitude in the deformation region.
[0020] Furthermore, step (6) is specifically as follows: deriving the friction coefficient of scratching under loads of 2N, 10N, and 50N from the friction testing machine respectively; selecting a time point in the steady-state strain stage, finding the strain size directly below the indenter at the corresponding time during the DIC strain analysis, and drawing the strain distribution curve of the TA1 surface layer along the scratching direction during the time.
[0021] Furthermore, step (8) is specifically as follows: within 200 μm in front of the indenter, when the strain difference between the maximum and minimum strain values of the material surface is ≥15%, local strain concentration occurs, and there is peeling and crack damage on the wear scar surface. At this time, the plastic rheology type is eddy current; and when the strain difference of the material surface within 200 μm in front of the indenter is <15%, the strain distribution is relatively uniform, and there is no peeling phenomenon on the wear scar surface. At this time, the plastic rheology type is laminar flow.
[0022] The present invention is achieved through the following technical scheme: pure titanium is selected as the research object, and the scratched surface and observation surface of the pure titanium are polished; a thin layer of white primer is sprayed on the observation surface with a spray gun, and then randomly distributed black paint spots are sprayed, a series of images of the changes in the spray spot surface during the scratching process are captured and recorded by a high-speed camera, and the images are subjected to DIC analysis to obtain the plastic rheological pattern during the scratching process.
[0023] Achievements and benefits of the present invention:
[0024] (1) This patent provides a DIC-based method for measuring the plastic rheological pattern induced by metal scratching. Through high-speed camera photography and DIC analysis, the strain change of the pure titanium surface under the action of scratching stress can be observed in real time. Combined with the wear scar morphology analysis, the plastic rheological pattern during the scratching process under different loads can be obtained, which is helpful for analyzing the surface deformation behavior and friction and wear mechanism of the material.
[0025] (2) This patent analyzes the strain changes under different scratch stresses and summarizes the strain field distribution, which is conducive to the study of surface modification technology to improve the wear resistance of pure titanium surface.
[0026] (3) This patented technology is mature and relatively simple to operate. It provides a new idea for studying the scratch-induced plastic rheological pattern of pure titanium surface, and is of great significance for studying the initiation and propagation behavior of microcracks at stress concentration points. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the scratched surface and observation surface of the sample.
[0028] Figure 2 This is a diagram of the high-speed camera, light source and friction machine setup.
[0029] Figure 3 Figure 2 shows the strain distribution diagram of DIC analysis under different loads and the strain distribution curve of the scratched surface along the scratching direction at a certain time point in the strain steady-state stage. The strain values directly below the scratching head at the selected time under different loads are circled in the figure; (a1) is the strain distribution diagram at 5.5 seconds under a 2N load, (a2) is the strain distribution curve at 5.5 seconds under a 2N load, (b1) is the strain distribution diagram at 6 seconds under a 10N load, (b2) is the strain distribution curve at 6 seconds under a 10N load, (c1) is the strain distribution diagram at 8.5 seconds under a 50N load, and (c2) is the strain distribution curve at 8.5 seconds under a 50N load.
[0030] Figure 4 The morphologies of wear scratches on the TA1 surface scratched under different loads; (a) is the morphology of wear scratches on the TA1 surface scratched under a load of 2N, (b) is the morphology of wear scratches on the TA1 surface scratched under a load of 10N, and (c) is the morphology of wear scratches on the TA1 surface scratched under a load of 50N. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0032] The present invention provides a method for measuring the plastic rheological mode introduced by metal scratching based on DIC, including using a high-speed camera to shoot the scratching process, using DIC technology to perform strain analysis, and observing the wear scar morphology and structure through SEM. A series of images of the surface spray spot changes of pure titanium during the scratching process are taken by a high-speed camera, and the images are subjected to DIC analysis to obtain the strain distribution during the scratching process. The wear scar morphology photographed by SEM is then combined with the strain field distribution to determine whether the plastic rheological type introduced by scratching under different loads is laminar flow or eddy current. This patent can observe the strain changes of the pure titanium surface under the action of scratching stress in real time, which is helpful for analyzing the surface deformation behavior and friction and wear mechanism of the material. This patent has mature technology and is relatively simple to operate. It provides a new idea for analyzing the plastic rheological mode introduced by metal scratching and the dynamic distribution of strain during the pure titanium scratching process. It is of great significance to study the surface deformation behavior of metal structural materials under different loads and the friction and wear mechanism of alloys, and is conducive to understanding the sliding flow field and deformation field in metals and improving the functional characteristics of metal surfaces.
[0033] A DIC-based measurement method for the plastic rheological mode induced by metal scratching uses a high-speed camera to capture and record a series of images of surface spray spot changes during scratching under different loads, and DIC analysis is performed on the images to obtain the strain distribution during the scratching process. The wear scar morphology is observed by SEM, corresponding to the strain field distribution, to determine the type of plastic rheological mode (eddy current, laminar flow) induced by scratching under different loads.
[0034] The average diameter of the spray spot is controlled below 20μm, and the spot distribution is controlled to occupy about 80% of the white paint area. Use a 0.5mm caliber spray gun to spray white paint, and a 0.18mm caliber spray gun to spray black paint.
[0035] The high-speed camera uses a five-fold lens as the magnification lens and a 100W LED light source as the illumination source. The image resolution is 2560×1920 and the frame rate is 200fps.
[0036] The strain analysis area of the titanium alloy surface is within 100μm thickness below the wear scar. When the load increases, the strain inhomogeneity increases, and the strain directly below the indenter increases with the increase of load. Within 200μm in front of the indenter, when the strain difference between the maximum and minimum strain of the material surface is ≥15%, local strain concentration occurs, and there is peeling and crack damage on the wear scar surface. At this time, the plastic rheology type introduced is eddy current; when the strain difference of the material surface within 200μm in front of the indenter is <15%, the strain distribution is relatively uniform, and there is no peeling phenomenon on the wear scar surface. At this time, the plastic rheology type introduced is laminar flow.
[0037] Example
[0038] (1) TA1 commercial pure titanium was cut into samples with a size of 5 mm × 5 mm × 2 mm as experimental objects.
[0039] (2) Spray spots on the observation plane of the sample. First, use a 0.5mm-caliber spray gun to spray a thin layer of white paint on the surface to achieve the effect of completely covering the metallic luster of the sample; then use a 0.18mm-caliber spray gun to spray black paint spots on the surface. The spots are randomly distributed, with an average diameter of less than 20μm, and the spots account for about 80% of the white paint area.
[0040] (3) Assemble a high-speed camera, select a five-fold lens as the magnifying lens, a 100 W LED light source as the illumination source, adjust the position of the camera and the friction tester, and change the focal length of the camera and the exposure time of the shooting until a clear and magnified image appears.
[0041] (4) A conical diamond scratching head with a tip angle of 120° and a diameter of 0.2 mm was used, the scratching speed was set to 0.1 mm / s, the scratching distance was set to 1 mm, the loading time was set to 10 s, the holding time was set to 5 s, and the scratching time was set to 10 s.
[0042] (5) Select loads of 2N, 10N, and 50N, set the image resolution to 2560×1920, the frame rate to 200fps, and the video saving time to 15s. Start the friction machine, press the scratching head into the sample surface and take the time before it starts to slide as the shooting starting point, and save the video after the 15s shooting time is over.
[0043] (6) Export the saved video files to tiff image format, sort and organize them, and import them into DIC analysis software. Select the strain change area within 100 μm thickness from the scratched surface, define the starting point, and calculate the strain size in the deformation area.
[0044] (7) The coefficient of friction (COF) of scratching under loads of 2N, 10N, and 50N was derived from the friction tester. A time point was selected at the steady-state stage of strain, such as Figure 3 As shown in the figure, the 5.5th second was selected for the 2N load, the 6th second was selected for the 10N load, and the 8.5th second was selected for the 50N load. In the DIC strain analysis, the strain magnitude directly below the indenter at the corresponding time was found, and the strain distribution curve of the TA1 surface layer along the scratching direction during the time was plotted.
[0045] (8) The morphology and structure of the wear scars on the surface of TA1 scratched under loads of 2N, 10N, and 50N were observed and analyzed by scanning electron microscope (SEM). Figure 4 shown.
[0046] (9) Summarize and analyze the scratch test results under different loads, explore the relationship between wear scar morphology and load size, and combine with DIC strain analysis results. According to the strain field distribution, the type of plastic rheology introduced by scratching under different loads can be determined. Figure 3 , Figure 4 The analysis shows that when the load increases, the strain inhomogeneity intensifies, and the strain directly below the indenter increases with the increase of load. Within 200μm in front of the indenter, when the strain difference between the maximum and minimum strain of the material surface is ≥15%, local strain concentration occurs, and there is peeling and crack damage on the wear scar surface. At this time, the plastic rheological type introduced is eddy current; when the strain difference of the material surface within 200μm in front of the indenter is <15%, the strain distribution is relatively uniform, and there is no peeling phenomenon on the wear scar surface. At this time, the plastic rheological type introduced is laminar flow.
[0047] The present invention successfully provides a new measurement method for the scratch-induced plastic rheological mode of the metal surface. The scratching process of industrial pure titanium under different loads is photographed with a high-speed camera, and then the strain change and stress field distribution in the deformation zone are calculated and analyzed by DIC software. The strain distribution is compared with the wear scar morphology observed by SEM, so as to determine the type of plastic rheology introduced by scratching under different loads. For example, when the strain is evenly distributed, laminar flow is introduced, and when the strain is locally concentrated, eddy current is introduced. This provides a new idea for the dynamic formation process of damage such as microcracks during the scratching process. The operation is relatively simple and has great application value.
Claims
1. A method for measuring the scratch-induced plastic rheological mode of a metal surface based on DIC, characterized in that: The steps include: Step (1): preparing a rectangular TA1 commercially pure titanium sample; Step (2): spraying a spot on the observation surface of the sample; Step (3): using the surface adjacent to the observation surface as the scratching surface; Step (4): applying scratches to the scratched surface by a friction tester, and recording the scratches with a high-speed camera to obtain a scratching video; Step (5): Calculate the strain magnitude in the deformation area based on the scratching video; Step (6): draw a strain distribution curve of the surface layer of TA1 along the scratching direction; Step (7): observing the morphology of the wear scar on the TA1 surface scratched under different loads by scanning electron microscopy; Step (8): Determine the type of plastic rheology.
2. The method according to claim 1, characterized in that The sample size in step (1) is 5±0.5 mm×5±0.5 mm×2±0.2 mm.
3. The method according to claim 2, characterized in that Step (2) is specifically as follows: use a 0.5 mm caliber spray gun to spray a layer of white paint on the surface so that the metallic luster of the sample is completely covered; then use a 0.18 mm caliber spray gun to spray black paint spots on the surface, the spots are randomly distributed, the average diameter is controlled below 20 μm, and the spot distribution occupies 80±5% of the white paint area.
4. The method according to claim 3, characterized in that The high-speed camera in step (4) selects a five-fold lens as the magnifying lens and a 100W LED light source as the illumination light source.
5. The method according to claim 4, characterized in that The scratching in step (4) is specifically performed by using a conical diamond scratching head with a tip cone angle of 120° and a diameter of 0.2 mm, setting the scratching speed to 0.1 mm / s, the scratching distance to 1 mm, setting the loading time to 10 s, the holding time to 5 s, and the scratching time to 10 s.
6. The method according to claim 5, characterized in that In step (4), a high-speed camera is used to record the scratching video, and the specific steps are as follows: loads of 2N, 10N, and 50N are selected, the image resolution is set to 2560×1920, the frame rate is set to 200fps, and the video storage time is set to 15s; Start the friction machine, press the scratching head into the sample surface and take the first second before it starts sliding as the shooting starting point. Save the video after the 15 second shooting time is over.
7. The method according to claim 6, characterized in that Step (5) is specifically as follows: sort and organize the scratching videos and import them into the DIC analysis program, select the strain change area within 100 μm thickness from the scratched surface, define the starting point, and calculate the strain size in the deformation area.
8. The method according to claim 7, characterized in that Step (6) is specifically as follows: derive the friction coefficient of scratching under loads of 2N, 10N, and 50N from the friction testing machine; select a time point in the steady-state strain stage, find the strain size directly below the indenter at the corresponding time during the DIC strain analysis, and draw the strain distribution curve of the TA1 surface layer along the scratching direction during this time.
9. The method according to claim 8, characterized in that Step (8) is specifically as follows: within 200 μm in front of the indenter, when the strain difference between the maximum and minimum strain values of the material surface is ≥15%, local strain concentration occurs, and there is peeling and crack damage on the wear scar surface. At this time, the plastic rheology type is eddy current; and when the strain difference of the material surface within 200 μm in front of the indenter is <15%, the strain distribution is relatively uniform, and there is no peeling phenomenon on the wear scar surface. At this time, the plastic rheology type is laminar flow.
Citation Information
Patent Citations
Device and method for measuring high-speed orthogonal cutting process strain through digital image correlation method
CN103394973A
Ultrahigh temperature multi-dimensional multi-functional strain measurement system based on ultraviolet imaging DIC and measurement method
CN107255454A
Method for forming scratchable image and scratchable image formed article
CN108388092A
Ultrasonic-assisted single-particle scratching test device and method
CN115647941A
Speckle coating film preparation method for strain analysis of flexible display screen and DIC test method
CN116037433A